Science and Information Literacy on the Internet: Using the ACRL and Project 2061 Standards to Create a Science Web Page Evaluation Tool ACRL Conference March 16, 2001 Denver, Colorado. - Kate Manuel (Issues in Science and Technology Librarianship)
This article reports on the "Science and Information Literacy on the Internet: Using the ACRL and Project 2061 Standards to Create a Science Web Page Evaluation Tool" presentation at the ACRL Conference, March 16, 2001, in Denver, Colorado.